Pelatihan Pembuatan Soal Kognitif Berbasis Aplikasi Android Kahoot untuk Guru Sekolah Dasar Islam Terpadu Bina Insani Kediri - Saidah, Karimatus; Mujiwati, Endang Sri; Permana, Erwin Putera; Wiguna, Frans Aditia; Damayanti, Susi; Mukmin, Bagus Amirul; Hunaifi, Abdul Aziz; Laila, Alfi; Basori, Muhamad; Wahyudi, Wahyudi; Kurnia, Ita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
This activity aims to provide training to teachers and practice problem making and implementation in elementary schools. So that teachers get direct experience in making problems through the Kahoot application for teachers. The method of carrying out this activity is carried out from the preparation stage to the reporting of activities that take about 1 month. Parties involved in the activity include: 1). Lecturers as speakers and moderators, students as a support team for the implementation of the event. 2). Teachers in SDIT Bina Insani Kediri. Of the 25 teachers who have participated in the training, as many as 17 teachers have submitted the results of the analysis, based on the results of the questionnaire showed 4 teachers stated there were no obstacles in implementing kahoot. While the other 13 stated to experience some obstacles, namely less accustomed to operating kahoot. The advantages of applications when implemented include more interesting and easy to do. Kahoot application can be one of the alternative learning variations. Through the use of kahoot learning outcomes related to the order of the level of truth problems can be more quickly known. Kahoot application is practical, because teachers can directly monitor students who work on problems.